2009
DOI: 10.1002/nbm.1378
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxygen and carbogen breathing on renal oxygenation measured by T2*‐weighted imaging at 3.0 T

Abstract: The aim of the study was to assess the influence of carbogen (95% O(2), 5% CO(2)) or pure oxygen breathing on renal oxygenation measured by blood oxygenation level dependent (BOLD) magnetic resonance imaging at 3.0 T. Seven healthy young volunteers (median age 25, range 23-35 years) participated in the study. A T2*-weighted fat-saturated spoiled gradient-echo sequence was implemented on a 3.0 T whole-body imager (TE/TR = 27.9 ms/49 ms, excitation angle 20 degrees ) with an acquisition time of approximately 5.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…It is also independent of signal intensity. Increasingly, human studies are examining R 2* with respect to tumor oxygenation, as shown for breast (34), prostate (35), head and neck tumors (36), and kidney (37). R 2* has been reported in a group of 31 breast cancer patients undergoing neoadjuvant chemotherapy (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also independent of signal intensity. Increasingly, human studies are examining R 2* with respect to tumor oxygenation, as shown for breast (34), prostate (35), head and neck tumors (36), and kidney (37). R 2* has been reported in a group of 31 breast cancer patients undergoing neoadjuvant chemotherapy (38).…”
Section: Discussionmentioning
confidence: 99%
“…We observed signal increases within 2–4 minutes, but little decline was seen within 90 seconds of return to air breathing. Previous studies have reported quite rapid signal decreases in breast (23) and normal kidneys (37) upon return to air‐breathing, but those studies used active flowing air as well as oxygen, whereas we used passive air and active flowing oxygen only. Thus, the bore of the magnet likely remained flooded with oxygen for some time after oxygen flow was discontinued.…”
Section: Discussionmentioning
confidence: 99%
“…Using a Levenberg–Marquardt algorithm on a voxel‐by‐voxel basis, the measured signal intensities in each voxel can be fitted to a two‐parameter equation [2]. We report T 1 and T2* rather than the reciprocal R 1 , R2* to provide direct comparison with previous reports in the literature for tissue values .…”
Section: Methodsmentioning
confidence: 99%
“…Although the data are not entirely consistent, most BOLD MRI studies in humans have demonstrated that breathing 100% oxygen increases intrarenal oxygenation in the medulla but not in the cortex, suggesting nonsaturation of renal medullary oxygenation under physiologic conditions. [13][14][15][16][17] Addition of a vasodilator gas exaggerates the medullary response but has a less consistent effect in the cortex. 13,15,16 In this regard, it is interesting to note that hyperbaric oxygen has been shown to exert a protective effect in an ischemia/reperfusion model in the rat.…”
mentioning
confidence: 99%
“…[13][14][15][16][17] Addition of a vasodilator gas exaggerates the medullary response but has a less consistent effect in the cortex. 13,15,16 In this regard, it is interesting to note that hyperbaric oxygen has been shown to exert a protective effect in an ischemia/reperfusion model in the rat. 18 …”
mentioning
confidence: 99%